The Role of Green Economy in Regional Tourism Development in Indonesia - Imleesh, Mohammed Mahmoud (Unram Journal of Community Service, 2025)
The primary aim of this research is to analyze and elucidate the pivotal role of the green economy in fostering sustainable regional development in Indonesia. As environmental concerns become increasingly pressing, understanding the intersection of economic growth and ecological sustainability is essential for effective policy-making. This study employs a systematic literature review (SLR) methodology, analyzing 22 scholarly journals through the PRISMA framework to ensure a comprehensive and rigorous examination of existing literature. The findings of this research provide compelling evidence that the implementation of green economic principles significantly contributes to the development of regional tourism in Indonesia. Furthermore, the study highlights the importance of collaboration with local communities, which not only enhances the effectiveness of green economic initiatives but also improves the quality of human resources. By integrating sustainable practices into regional development strategies, this research underscores the potential for the green economy to drive both economic growth and environmental stewardship in Indonesia.